Observer‐based fuzzy adaptive control for MIMO nonlinear systems with non‐constant control gain and input delay - Jipeng Zhao; Shaocheng Tong; Yongming Li (IET Control Theory & Applications, 2021)
Abstract In this work the fuzzy adaptive control issue is investigated for multiple‐input multiple‐output (MIMO) uncertain nonlinear systems in strict‐feedback form. The controlled systems under consideration of this work contain the immeasurable states, unknown control gain functions and input time delays. The immeasurable states are estimated by constructing a fuzzy state observer, and the uncertain nonlinear functions are approximated by utilizing the fuzzy logic systems (FLSs). In addition, the Pade approximation method is employed to handle the input time delays problem. An observer‐based fuzzy adaptive centralized control algorithm is presented by employing the adaptive backstepping control design technique and constructing the Logarithm Lyapunov functions. The designed fuzzy adaptive robust control algorithm can make sure that all signals in the closed‐loop system are semi‐globally uniformly ultimately boundedness (SGUUB). Finally, a numerical simulation example and a practical system example are considered to testify the availability of the designed centralized controllers.